New Paradigm in The Treatment of Cyberbullying Crimes Through an Integrated Cyberbullying Prevention: A Non-penal Policy in Indonesia - Sufi Amalia, Cici Riski; Anggraini, Arista Ulfa; Rato, Dominikus; Setyawan, Fendi (JURNAL LEGALITAS, 2024)
Technological advancements have led to the emergence of new digital crimes, one of the most pressing being cyberbullying, which has become a significant issue requiring urgent attention. The impact of cyberbullying extends beyond physical and psychological harm to victims, necessitating a response that goes beyond mere prosecution or repressive measures. In Indonesia, existing legal provisions addressing cyberbullying are inadequate, leaving room for improvement in both legal frameworks and preventive strategies. This study aims to identify the gaps in Indonesian legislation concerning cyberbullying and propose integrated strategies for its prevention. Using a juridical-normative research approach, the study reveals that while cyberbullying is addressed in several existing laws and regulations, there is a lack of specific, explicit provisions that comprehensively define the crime's elements. As a result, the legal framework remains insufficient to effectively combat cyberbullying. To address this, the research advocates for an integrated approach to cyberbullying prevention that combines technological solutions with educational initiatives. This includes enhancing parental control features on smartphones and computer applications to block harmful content and promoting community awareness through education, counselling, and public campaigns. Additionally, the establishment of a dedicated cybercrime division by the Indonesian National Police is recommended to improve the enforcement and prosecution of cyberbullying offences.